Molecular Mechanism of Tetrabromobisphenol A (TBBPA)-induced Target Organ Toxicity in Sprague-Dawley Male Rats - Choi, Jae Seok (The Korean Society of Toxicology, 2011)
Brominated flame retardants (BFRs) are present in many consumer products ranging from fabrics to plastics and electronics. Wide use of flame retardants can pose an environmental hazard, which makes it important to determine the mechanism of their toxicity. In the present study, dose-dependent toxicity of tetrabromobisphenol A (TBBPA), a flame retardant, was examined in male prepubertal rats (postnatal day 18) treated orally with TBBPA at 0, 125, 250 or 500 mg/kg for 30 days. There were no differences in body weight gain between the control and TBBPA-treated groups. However, absolute and relative liver weights were significantly increased in high dose of TBBPA-treated groups. TBBPA treatment led to significant induction of CYP2B1 and constitutive androstane receptor (CAR) expression in the liver. In addition, serum thyroxin (T4) concentration was significantly reduced in the TBBPA treated group. These results indicate that repeated exposure to TBBPA induces drug-metabolising enzymes in rats through the CAR signaling pathway. In particular, TBBPA efficiently produced reactive oxygen species (ROS) through CYP2B1 induction in rats. We measured 8-hydroxy-2'-deoxyguanosine (8-OHdG), a biomarker of DNA oxidative damage, in the kidney, liver and testes of rats following TBBPA treatment. As expected, TBBPA strongly induced the production of 8-OHdG in the testis and kidney. These observations suggest that TBBPA-induced target organ toxicity may be due to ROS produced by metabolism of TBBPA in Sprague- Dawley rats.